A proof-of-concept study to investigate the radiolabelling of human mesenchymal and hematopoietic stem cells with [89Zr]Zr-Df-Bz-NCS - Maryke Kahts; Juanita Mellet; Chrisna Durandt; Kinosha Moodley; Beverley Summers; Thomas Ebenhan; Jan Rijn Zeevaart; Omer Aras; Michael S. Pepper (SpringerOpen, 2024)
Abstract Background The transplantation of hematopoietic stem and progenitor cells (HSPCs) or mesenchymal stromal/stem cells (MSCs) for the treatment of a wide variety of diseases has been studied extensively. A challenge with cell-based therapies is that migration to and retention at the target site is often difficult to monitor and quantify. Zirconium-89 (89Zr) is a positron-emitting radionuclide with a half-life of 3.3 days, which allows long-term cell tracking. Para-isothiocyanatobenzyl-desferrioxamine B (Df-Bz-NCS) is the chelating agent of choice for 89Zr-cell surface labelling. We utilised a shortened labelling method, thereby avoiding a 30-60-min incubation step for [89Zr]Zr-Df-Bz-NCS chelation, to radiolabel HSPCs and MSCs with zirconium-89. Results Three 89Zr-MSC labelling attempts were performed. High labelling efficiencies (81.30 and 87.30%) and relatively good labelling yields (59.59 and 67.00%) were achieved with the use of a relatively larger number of MSCs (4.425 and 3.855 million, respectively). There was no significant decrease in MSC viability after 89Zr-labeling (p = 0.31). This labelling method was also translatable to prepare 89Zr-HSPC; preliminary data from one preparation indicated high 89Zr-HSPC labelling efficiency (88.20%) and labelling yield (71.06%), as well as good HSPC viability after labelling (68.65%). Conclusions Successful 89Zr-MSC and 89Zr-HSPC labelling was achieved, which underlines the prospects for in vivo cell tracking studies with positron emission tomography. In vitro investigations with larger sample sizes and preclinical studies are recommended.